New boundary conditions for simulating the filling stage of the injection molding process - Galuppo, Wagner de Campos (2020)
Purpose The purpose of this paper is to develop new boundary conditions for simulating the injection molding process of polymer melts. Design/methodology/approach The boundary conditions are derived and implemented to simulate real-life air vents (used to allow the air escape from the mold). The simulations are performed in the computational libraryOpenFOAM (R) by considering two different fluid models, namely, Newtonian and generalized Newtonian (Bird-Carreau model). Findings A detailed study on the accuracy of the solverinterFoamfor simulating the filling stage is presented, by considering simple geometries and adaptive mesh refinement. The verified code is then used to study the three-dimensional filling of a more complex geometry. Originality/value The results obtained showed that the numerical method is stable and allows one to model the filling process, simulating the real injection molding process.